Radio Echo-Sounding of Spitsbergen Glaciers: Problems in the Interpretation of Layer and Bottom Returns - Dowdeswell, J. A.; Drewry, D.J.; Liestøl, O.; Orheim, O. (Journal of Glaciology, 1984)
Abstract Airborne radio echo-sounding of Spitsbergen glaciers during 1980 used 60 MHz SPR1 Mk IV equipment. On several glaciers results showed unambiguous bottom returns at depths 2–3 times those reported in previous Soviet echo-sounding at 440 and 620 MHz. Comparison of 60 MHZ records and independent gravity-surveyed ice thickness for two glaciers agreed to within 10%, whereas Soviet ice thicknesses were only 30–60% of gravity depths. Soviet bed echoes often coincided closely with an internal reflecting horizon recorded by the SPRI Mk IV system, and it is shown that Soviet U.H.F. equipment failed to penetrate to the true glacier bed on a number of ice masses (e.g. Finsterwalderbreen, Kongsvegen, Negribreen). This was probably due to increased absorption and scattering at higher radio frequencies, related to the inhomogeneous nature of Spitsbergen glaciers, which are often at or near the pressure-melting point. Both 60 MHz and U.H.F. equipment seldom recorded bed echoes in ice-cap accumulation areas (e.g. Isachsenfonna), where firn soaking during summer and 10 m temperatures of zero degrees have been observed. An isolated internal reflecting horizon was recorded on many glaciers. It is unlikely to be a moraine layer, but may be related to ice with a water content of 1–2% observed at a similar depth (115 m) in a drill core from Fridtjovbreen.